Risk of Hepatitis E among Persons Who Inject Drugs in Hong Kong: A Qualitative and Quantitative Serological Analysis - Siddharth Sridhar; Nicholas Foo-Siong Chew; Jianwen Situ; Shusheng Wu; Ernest Sing-Hong Chui; Athene Hoi-Ying Lam; Jian-Piao Cai; Vincent Chi-Chung Cheng; Kwok-Yung Yuen (Microorganisms, 2020)
Hepatitis E virus (HEV) is an important cause of hepatitis, which can be transmitted via the bloodborne route. However, risk of hepatitis E among persons who inject drugs (PWIDs) is poorly understood. This study aimed to elucidate whether PWIDs are at risk for hepatitis E. We performed HEV IgM, IgG and nucleic acid detection on a cohort of 91 PWIDs and 91 age- and sex-matched organ donors. Blood HEV IgG was measured using the WHO HEV antibody standard. The effects of age, gender and addictive injection use on HEV serostatus and concentration were assessed. HEV IgG seroprevalence was 42/91 (46.2%) in the PWID group and 20/91 (22%) in the donor group (odds ratio = 3.04 (1.59–5.79), p = 0.0006). The median HEV IgG concentration was 5.8 U/mL (IQR: 2.5–7.9) in the PWID group and 2.1 U/mL (IQR: 1.2–5.3) in the donor group (p = 0.005). Increasing age and addictive injection use were significantly associated with HEV IgG serostatus, but only addictive injection use was associated with HEV IgG concentration (p = 0.024). We conclude that PWIDs are at increased risk for hepatitis E and are prone to repeated HEV exposure and reinfection as indicated by higher HEV IgG concentrations.